How AI tools can—and cannot—help organizations become more ethical - De Cremer, David; Narayanan, Devesh (Frontiers in Artificial Intelligence, 2023)
In this paper, we argue that we cannot expect that AI systems – even given more data or better computational resources – will be more ethical than the humans who develop, deploy and use them. As such, we advocate that it is necessary to retain the responsibility for ethical decision-making in human hands. In reality, however, human decision-makers currently do not have the ethical maturity to meaningfully take on this responsibility. So, what to do? We develop the argument that to broaden and strengthen the ethical upskilling of our organizations and leaders, AI has a crucial role to play. Specifically, because AI is a mirror that reflects our biases and moral flaws back to us, decision-makers should look carefully into this mirror – taking advantage of the opportunities brought about by its scale, interpretability, and counterfactual modeling – to gain a deep understanding of the psychological underpinnings of our (un)ethical behaviors, and in turn, learn to consistently make ethical decisions. In discussing this proposal, we introduce a new collaborative paradigm between humans and AI that can help ethically upskill our organizations and leaders and thereby prepare them to responsibly navigate the impending digital future.